Age-Onset-Related Particularities of Pediatric MS—Understanding the Spectrum: A Tertiary Center Experience - Alice Denisa Dică; Dana Craiu; Florentina Ionela Linca; Magdalena Budișteanu; Catrinel Iliescu; Carmen Sandu; Cristina Pomeran; Diana Bârcă; Niculina Butoianu; Carmen Burloiu; Ioana Minciu; Ina Ofelia Focșa; et al. (Diseases)
Background: Pediatric-onset multiple sclerosis (POMS) is a rare and heterogeneous condition, with clinical features, progression, and therapeutic response varying significantly according to age at onset. Early-onset MS (<10 years) presents particular diagnostic and management challenges due to atypical presentations and more active inflammatory profiles. Objectives: To identify age-related clinical, radiological, and therapeutic characteristics of pediatric MS, with a specific focus on early-onset cases, and to compare them with intermediate (10–12 years) and late-onset (>12 years) forms. Methods: We conducted a retrospective analysis of medical records from 120 pediatric patients diagnosed with MS at a tertiary neurology center between 2018 and 2024. Patients were grouped by age at onset and assessed for clinical presentation, number and timing of relapses, EDSS scores, imaging findings, and treatment patterns. Results: Early-onset MS was associated with atypical symptoms, delayed diagnosis, more frequent relapses, and multifocal brainstem and cerebellar involvement. The diagnosis was significantly delayed in younger children compared to adolescents. EDSS scores tended to remain stable in the first 2–3 years, but early-onset patients showed a notable decline after the fourth year. While most patients received disease-modifying therapies, high-efficacy agents were underused due to age-related restrictions. Intermediate-onset patients presented overlapping features of both early and late-onset MS and had the highest proportion of fully preserved motor function (EDSS 0) at the end of follow-up. MRI findings revealed more extensive and confluent lesions in younger patients, particularly in the first two years after onset. Conclusions: Age at disease onset is a key determinant of clinical course and treatment response in pediatric MS. Early recognition and timely initiation of appropriate therapy—especially high-efficacy agents—may improve outcomes and reduce long-term disability. Further multicenter studies with standardized imaging and cognitive assessment protocols are needed to optimize care for this vulnerable population.